An unexpected role of CLASP1 in radiation response and S-phase regulation of head and neck cancer cells - Reinout H. de Roest; Marijke Buijze; Myrthe Veth; Klaas de Lint; Govind Pai; Martin A. Rooimans; Rob M.F. Wolthuis; Arjen Brink; Jos B. Poell; Ruud H. Brakenhoff (PLoS ONE, 2025)
Radiotherapy is a mainstay of treatment for head and neck squamous cell carcinoma (HNSCC), either definitive or adjuvant to surgery. Biological factors known to affect radiation response are hypoxia and DNA repair capacity, but several lines of evidence indicate that other genes and pathways in the tumor cells might be involved that have not been elucidated. Here, we report the results of a genome-wide CRISPR-Cas9 functional genomics screen in HNSCC cells to identify radiosensitizing genes. Remarkably, microtubule organizing genes were identified with CLASP1 as most unexpected radiosensitizing hit. Clonogenic assay confirmed the radiosensitizing effect of CLASP1 knockout. Functional analysis showed that CLASP1 knockout has major impact during S-phase, and resulted in mitotic cells with broken chromosomes and cell death. CLASP1 and possibly the microtubule machinery in broader sense seem involved in protection of HNSCC cells against radiation–induced DNA damage. This newly identified mechanism provides an outlook for novel treatment approaches in HNSCC.